Small is not Always Beautiful: A Case Study of the Njinikom Area Development Association (Nordic Journal of African Studies, 2002)
Small, it is often claimed, is beautiful. This adage informs basismo, a strategy being used to promote the bottom-top development approach. The World Bank's bias for local development associations is premised on this same normative assumption. This case study of the Njiinkom Development Association (NADA) examines the truth claims of this adage and seeks to make connections between the local, national and global developments, revealing only their dynamics but uncovering how these mediate the defining of selfhood among NADA members. NADA, it is argued, is also a space for violence (symbolic) engendered by the conflict of two rationalities and the penchant for politicizing even economic issues. Outcomes of struggles are skewed in favour of elites who are empowered with symbolic capital and money. Differential empowerment gives them an advantage that is used in promoting the birth of a new consciousness. Its effects are far reaching as they breach all accepted and acceptable protocol. Furthermore, it shows that elites are willing to invest in the development of the village only if it is a win-win game. Present development strategies seem to gloss over most of these considerations, thus impairing their effectiveness. Reversal of this trend with a view to promoting sustainable development in "village societies" such as Njinikom that are culturally different would require a conversation.